Formulation and Evaluation of Transdermal Gel of Ibuprofen: Use of Penetration Enhancer and Microneedle: Formulation and Evaluation of Transdermal Gel of Ibuprofen - Parhi, Rabinarayan; Venkata Sai Goutam, Sahukara; Mondal, Sumanta (Iranian Journal of Pharmaceutical Sciences, 2020)
The objective of the current study was to develop Ibuprofen (IBP) gel using different polymers individually and in combination and then to select best gel formulation based on various in-vitro evaluation parameters such as bioadhesive strength, gel strength, spreadability, viscosity and drug release study. The selected gel formulation was found to be composed of 1% (w/w) each of hydroxypropyl methylcellulose (HPMC K100M) and sodium carboxy methylcellulose (NaCMC). Two techniques such as chemical method using 1,8-cineole as chemical penetration enhancer (CPE) and physical technique using microneedle were employed to improve IBP permeation across the abdominal skin of rat. Out of the two techniques, the later technique showed higher (2.865-fold) permeation enhancement compared to control. Furthermore, a synergistic effect was also observed when both the techniques were used simultaneously with 3.307-fold increase in permeation enhancement. Invivo anti-inflammatory study on rats induced with carrageenan paw oedema and analgesic activity investigation by tail flick method in rat model exhibited sustained effect up to 8 h compared to orally treated group. The stability study at room and accelerated conditions for three months did not show any sign of instability. Thus, the developed IBP gel is stable and have potential to illicit both anti-inflammatory and analgesic effect when administered transdermally.